“Nossa pastora”: entre o “estabelecido” e o “vivido” no cotidiano religioso da liderança feminina na Igreja Assembleia de Deus em Raposa – MA - CANUTO, Valquíria Sousa (2023)
This study aims to understand gender relations within the family and religious contexts based on the leadership roles performed by Pastors' Wives in Assemblies of God churches in the municipality of Raposa, metropolitan region of São Luís - MA. In Pentecostal churches, particularly in the Assemblies of God, women's participation in religious activities is disproportionately higher compared to men's participation. After identifying some activities carried out by these women, it was observed that they hold strong leadership positions within the analyzed network of Assemblies of God. However, despite their significant roles as leaders, they are not allowed to hold the position of female pastors due to the Pentecostal-Assembly of God doctrine followed by the researched churches. Through participation in women's activities in the churches, informal conversations, and semi-structured interviews conducted with Pastors' Wives and women attending the church, it was possible to observe that by performing the activities they engage in they fulfill their role as "helpers" to their husbands in their pastoral duties. Nevertheless, even though they do not hold the title of pastors and are not remunerated for their activities, in their everyday lives, they exercise pastoral functions through the activities they carry out with women.